IMPLEMENTASI GAMIFIKASI SEBAGAI STRATEGI INOVATIF DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KOMPUTASIONAL PADA ANAK USIA DINI - Wijayanti, Asti; Hamidah, Siti; Yayuk, Erna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and test the effectiveness of gamification as an innovative strategy in improving computational thinking skills in early childhood. Using a mixed methods approach and quasi-experimental design, the study involved 30 children aged 5-6 years from Aisyiyah Bustanul Athfal 32 Kindergarten in Malang City, who were divided into an intervention group (gamification) and a control group (traditional learning). Data collection instruments included computational thinking tests, observations, and interviews. The results showed a significant increase in the average score in the intervention group (from 65.2 to 82.4), compared to the control group (from 64.8 to 70.1), with the highest increase in the aspects of algorithms and problem solving. The discussion integrated Piaget's cognitive development theory and Deterding's gamification, which confirmed that game elements increase children's intrinsic motivation. The conclusion of the study is that gamification is effective for building children's cognitive foundations in the digital age, with suggestions for improvement such as teacher training and collaborative application development, as well as recommendations for further research with larger samples and longer durations.